Cost-efficiency improvement of bivalves shells preparation when tracing their geographic origin through ICP-MS analysis of elemental fingerprints - Ricardo, Fernando (2020)
Developing methodologies employed to trace the geographic origin of seafood as accurate and fast as possible can help to speed-up the delivery of results to legal authorities, reduce associated costs and minimize environmental impacts (associated with the residues generated). The present study evaluated if trace element fingerprints (TEF) of a small homogenized subsample of Manila clams (Ruditapes philippinarum) right valve yielded a representative elemental signature of the whole shell. Four elemental ratios (Ba/Ca, Mg/Ca, Mn/Ca and Sr/Ca) commonly employed to trace the geographic origin of bivalves were determined from subsamples of 0.2 and 3 g of the homogenized right valve and the whole left valve (4 g). A Canonical Analysis of Principal Coordinates developed for the subsamples of small portions (0.2 g) of the homogenized right valve revealed an accuracy of 100%, that led to the correct classification of the subsample of 3 g to their respective valve and that of 4 g to its matching shell. Results achieved indicate that TEF of a small homogenized portion of a bivalves valve is representative of the whole shell and can be employed to provide an accurate, fast, reliable and environmentally safer method to trace its geographic origin.